2021
DOI: 10.1101/2021.06.18.21259157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical profiles at the time of diagnosis of COVID-19 in Costa Rica during the pre-vaccination period using a machine learning approach

Abstract: Background: The clinical manifestations of COVID-19 disease, caused by the SARS-CoV-2 virus, define a large spectrum of symptoms that are mainly dependent on the human host conditions. In Costa Rica, almost 319 000 cases have been reported during the first third of 2021, contrasting to the 590 000 fully vaccinated people. In the pre-vaccination period (the year 2020), this country accumulated 169 321 cases and 2185 deaths. Methods: To describe the clinical presentations at the time of diagnosis of COVID-19 in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Nevertheless, this benefit could be no strong enough with the introductions of other lineages such as the lineages A.2.5, A.2.5.1 and, A.2.5.2 (with high frequency in Central America) which were predominant during 2021, and later with the arrival of the alpha and gamma variants. In addition, our previous work demonstrated that the clinical manifestations of COVID-19 in Costa Rican cases were independent of the SARS-CoV-2 lineages, including no differences for the lineage B.1.1.389 and the mutation S:T1117I (Molina-Mora, González, et al, 2021). COVID-19 disease, as an infection disease, depends not only on the viral agent (SARS-CoV-2 genotype), but also on the host conditions (genetics and risk factors) and the environment (social behavior) (Molina-Mora, González, et al, 2021;Tsui, Deng, & Pan, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, this benefit could be no strong enough with the introductions of other lineages such as the lineages A.2.5, A.2.5.1 and, A.2.5.2 (with high frequency in Central America) which were predominant during 2021, and later with the arrival of the alpha and gamma variants. In addition, our previous work demonstrated that the clinical manifestations of COVID-19 in Costa Rican cases were independent of the SARS-CoV-2 lineages, including no differences for the lineage B.1.1.389 and the mutation S:T1117I (Molina-Mora, González, et al, 2021). COVID-19 disease, as an infection disease, depends not only on the viral agent (SARS-CoV-2 genotype), but also on the host conditions (genetics and risk factors) and the environment (social behavior) (Molina-Mora, González, et al, 2021;Tsui, Deng, & Pan, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, our previous work demonstrated that the clinical manifestations of COVID-19 in Costa Rican cases were independent of the SARS-CoV-2 lineages, including no differences for the lineage B.1.1.389 and the mutation S:T1117I (Molina-Mora, González, et al, 2021). COVID-19 disease, as an infection disease, depends not only on the viral agent (SARS-CoV-2 genotype), but also on the host conditions (genetics and risk factors) and the environment (social behavior) (Molina-Mora, González, et al, 2021;Tsui, Deng, & Pan, 2020). Thus, this work represents another piece to understand the dynamics of the COVID-19 pandemic in Costa Rica, in this case focused on the virus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The SARS-CoV-2 virus, responsible for the COVID-19 pandemic, has been detected in more than 181 million people worldwide and more than 365,000 cases in Costa Rica (with at least 4650 deaths) until June 30th, 2021. As part of the epidemiological surveillance of the pandemic in Costa Rica, we have studied both genomic features of the virus and clinical and demographic patterns among diagnosed patients ( Molina-Mora et al, 2021a ; Molina-Mora et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%